Wewenang Presiden dalam Pemberian Grasi Kepada Terpidana Warga Negara Asing : (Studi Kasus Pemberian Grasi oleh Presiden ke Enam Republik Indonesia, Susilo Bambang Yudhoyono Kepada Schapelle Corby; dalam Kasus Penyelundupan Ganja dari Australia) - Alezandro Gerald Tokoh; Saryono Yohanes; Hernimus Ratu Udju (Pusat Riset dan Inovasi Nasional, 2024)
The granting of clemency is a constitutional authority vested in the president, allowing the reduction of sentences or the release of convicts. This study aims to examine the authority of the Indonesian president in granting clemency to foreign convicts, with a case study on President Susilo Bambang Yudhoyono's clemency granted to Schapelle Corby, an Australian citizen involved in a marijuana smuggling case. This study uses a normative juridical approach with an analysis of the laws and regulations governing clemency, as well as a review of the political, legal, and diplomatic aspects influencing the president's decision. The research also utilizes secondary data such as legal documents, journal articles, and relevant media reports. The findings indicate that the president's authority to grant clemency, including to foreign nationals, is regulated by the constitution and clemency laws. The clemency granted to Schapelle Corby was influenced by various considerations, including diplomatic pressure from the Australian government, the convict's health condition, and humanitarian factors. This decision elicited various public reactions, both supportive and opposing, with arguments encompassing legal, ethical, and national interest aspects. The study concludes that although the president has full authority to grant clemency, the exercise of this power should take into account broader factors, including its impact on international relations and public perception of the judicial system. This case study provides important insights into the dynamics between law and politics in the practice of granting clemency in Indonesia.